Taste and Fashion: Three Philosophical-Anthropological Comparative Readings (Itinera, 2017)
âFollowing current fashionsâ is a widespread and well-known phenomenon of so called âconsumer societyâ, characterized by a rapid change of shared tastes. Although philosophy has not paid enough attention to this phenomenon yet, references to fashion or evaluations of its intrinsic dynamics are present in the works of several contemporary philosophers. Concerning this matter, the purpose of the paper is to compare conceptual paradigms emerging from the perspectives of three twentieth-century thinkers: Nicolai Hartmann, Hans- Georg Gadamer and Eugen Fink.Â Â Â